Ergonomics and Tri Hita Karana Conception in Balinese Traditional Houses - I Nyoman Artayasa (Institut Seni Indonesia Denpasar, 2010)
Tri Hita Karana is the concept of three things that can lead to happiness, which consist of the relationship of human beings with God, amongst human beings, and the relationship of human beings with the environ- ment, which is embodied in the circulation, the design space forming element, the supporting build a space, design of facilities, utilities and decoration. The study of ergonomics on traditional residential houses in Bali focuses on task elements, organization and environment. The task examines how the facilities are created based on anthropometric and activity flow. The organization studies about traditional Balinese buildings layout in terms of organization of space, which resulted in a large scale, function space and circulation space. Environment review the two sides, firstly is physical environment, namely: the use of circulation, lighting and handling the existing season every year, and secondly is the social environment, namely: religion, beliefs, norms and others. There are similarities between Ergonomics and Tri Hita Karana, therefore this study intend to it. It is conducted by using qualitative descriptive analysis with the applica- tion of Tri Hita Karana concept on traditional Balinese buildings and also accompanied with ergonomic values based on te ape ape ape ape ape ape ape ape ape ape ape ape ape ape ape appose of this writing is to observe whether the ergonomics and Tri Hita Karana have similar views in the embodiment of traditional Balinese houses. In the end of the discussion we can conclude that the embodiment of traditional Balinese residential buildings has to be considered on the relationship of human beings with God and also the relationship of human being with the environment. It is also includes a consideration in ergonomics con- sists of: task, organization and environment; and it is found out that in the concept of Tri Hita Karana has similarities with the concept of ergonomics on traditional Balinese houses.